2017
DOI: 10.5152/eej.2017.17018
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical and Biological Properties of a New Portland Cement-based Root Repair Material

Abstract: Objective: To propose bismuth carbonate, a radiopacifying agent, as a new endodontic root repair material that was added to Portland cement (PC) at 2 wt%, 5 wt%, 10 wt% and 15 wt%, and physicochemical and biological properties of each formulation were evaluated in comparison to MTA-Angelus. Methods: Mixed and powder samples were analysed by scanning electron microscopy (SEM) and X-ray power diffraction (XRD), and the semiquantitative constitution of the powder was determined by energy-dispersive spectrometer (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…At the 6 th hour interval and after the anesthesia effect subsided, there were significantly high post-instrumentation pain levels that increased and peaked at the 12 th hour and declined gradually thereafter. This is in accordance with several studies (14,(24)(25)(26)(27) where high pain scores were recorded by the patients at the first 24 hours and then decreased considerably in the subsequent follow-up time points. This recorded pain might be attributed to the expression of pro-inflammatory mediators such as prostaglandins, leukotrienes, serotonin, histamine and bradykinin (pain mediators) and neuropeptides such as substance P and calcitonin gene-related peptide from C-type nerve fibers present in the periodontal ligament following instrumentation of the root canal which initiate inflammatory responses during the first 24 hours and recedes thereafter (28)(29)(30)(31) .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…At the 6 th hour interval and after the anesthesia effect subsided, there were significantly high post-instrumentation pain levels that increased and peaked at the 12 th hour and declined gradually thereafter. This is in accordance with several studies (14,(24)(25)(26)(27) where high pain scores were recorded by the patients at the first 24 hours and then decreased considerably in the subsequent follow-up time points. This recorded pain might be attributed to the expression of pro-inflammatory mediators such as prostaglandins, leukotrienes, serotonin, histamine and bradykinin (pain mediators) and neuropeptides such as substance P and calcitonin gene-related peptide from C-type nerve fibers present in the periodontal ligament following instrumentation of the root canal which initiate inflammatory responses during the first 24 hours and recedes thereafter (28)(29)(30)(31) .…”
Section: Discussionsupporting
confidence: 93%
“…Also, One Shape system resulted in a high intensity of postoperative pain after using it, which was not statistically significant when compared to ProTaper Next multi-file system and statistically significant when compared to Revo-S multi-file system (36) . The results of other studies revealed that there was no difference in postoperative pain between the single-file and multi-file root canal instrumentation techniques evaluated in their researches (25,26) .…”
Section: Discussionmentioning
confidence: 92%
“…2Shape rotary system (MicroMega, Besancon, France) has been introduced to the market as a new rotary system consisting of two shaping files which have been heat-treated representing the T-Wire technology [7]. While, Neoniti (Neolix, Châtres-la-Forêt, France) NiTi rotary system is manufactured by cutting a wire through electrical discharge machining process [8]. The manufacturer assumed that it has controlled memory and a rough surface, resulting in satisfactory shaping and no screwing effect.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to study design, most studies were parallel, and they were performed at university settings. The mean age reported was 36.1 years (Arslan et al 2016, Gathani et al 2016, Jain et al 2016, Neves et al 2016, Aqrabawi & Jamani 2006, Çiçec et al 2017, Dourado et al 2005, Gomes et al 2017, Kashefinejad et al 2016, Kherlakian et al 2016, Mollashahi et al 2017, Neelakantan et al 2015, Peters et al 2004, Relvas et al 2016, Shokraneh et al 2017, Topcuoglu et al 2017, Wei et al 2006; and female patients prevailed in 13 studies (Comparin et al 2017, Neves et al 2016, Pasqualini et al 2016, Aqrabawi & Jamani 2006, Dourado et al 2005, Gomes et al 2017, Dourado et al 2005, Gomes et al 2017, Peters et al 2004, Wei et al 2006, Aminsobhani et al 2017, Krithikadatta et al 2016, Saumya-Rajesh et al 2017.…”
Section: Studies Characteristicsmentioning
confidence: 99%
“…Different instruments were used to perform the endodontic treatment, such as manual K-files, rotatory instruments The predominant teeth treated was molar (Arslan et al 2016, Gathani et al 2016, Jain et al 2016, Nekoofar et al 2015, Aqrabawi & Jamani 2006, Gomes et al 2017, Kherlakian et al 2016, Neelakantan et al 2015, Relvas et al 2016, Shokraneh et al 2017, Wei et al 2006, Aminsobhani et al 2017, Krithikadatta et al 2016, Saumya-Rajesh et al 2017, Dalton et al 1998, Gambarini et al 2017, Pettiette et al 2001, Saha et al 2018, Shahi et al 2016, Zhou et al 2013.…”
Section: Studies Characteristicsmentioning
confidence: 99%